Keabsahan Transaksi Jual Beli Properti Menggunakan Sistem Pre Project Selling Ditinjau Dari Hukum Perjanjian (Studi Kasus Proyek Meikarta Cikarang Kabupaten Bekasi) - Ahmad Syauqi Robbi; Muhammad Yasir (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study discusses the sale and purchase of property transactions using the pre-project sales system in terms of the legal agreement and the responsibility of the legal developer (developer) for units of buyers of Meikarta property units in the Pre-Sale Project. The research method used in this study is a normative research method. The research data was collected by means of a literature study through a research method of the law that discusses Law Number 20 of 2011 concerning Flats. The results of this study indicate that the binding purchase agreement (PPJB) of Meikarta apartment units involving the parties between the developer (developer) and the buyer is illegal and null and void, because the required conditions have not yet been fulfilled. The requirements specified in Article 1320 of the Law Law Civil. The developer (developer) can be held accountable for Acts Against the Law (PMH) by the buyer approved in Article 1365 of the Civil Code which discusses all aspects of legality (licensing) in accordance with Law Number 20 of 2011 concerning Flats, developers (developers) before building apartments, such as the Environmental Impact Analysis Permit and Building Permit have not yet been approved by the developer.Keywords: Responsibility, Developer, Seling Per Project.